Influential factors on intention to quit smoking among youth male smokers in UiTM Cawangan Melaka Kampus Bandaraya Melaka / Nurul Aishah Mohd Noor - Mohd Noor, Nurul Aishah (Faculty of Business and Management, 2019)
The conduct of this study is aimed to identify the influential factors on intention to quit smoking among youth male smokers in UiTM Cawangan Melaka Kampus Bandaraya Melaka and it was done based on the Theory of Planned Behavior (TPB) proposed by Icek Ajzen in 1985. Non-probability under purposive sampling was employed for the study and questionnaire was used as the core to collect the data. The questionnaire was distributed via QR code and Google Form link over a period of 2 weeks from 27th April until 11th May 2019. At the end of the time frame, a total of 116 usable questionnaires were collected and they were then keyed in and analysed using the SPSS software version 22. According to the data analysis, two of the independent variables which are attitude and perceived behavioral control were found to have significant relationships with intention to quit smoking. Meanwhile, it was found that subjective norms do not have a significant relationship with intention to quit smoking. Based on the findings, several recommendations have been made at the end of the report, proposing for the Malaysian government and for the future researchers.